2014
DOI: 10.1002/pdi.1835
|View full text |Cite
|
Sign up to set email alerts
|

Low carbohydrate diet to achieve weight loss and improve HbA1c in type 2 diabetes and pre‐diabetes: experience from one general practice

Abstract: Patients with diabetes have long been exhorted to give up sugar, encouraged instead to take in fuel as complex carbohydrate such as the starch found in bread, rice or pasta (especially if ‘wholemeal’). However, bread has a higher glycaemic index than table sugar itself. There are no essential nutrients in starchy foods and people with diabetes struggle to deal with the glycaemic load they bring. The authors question why carbohydrate need form a major part of the diet at all. The central goal of achieving subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 11 publications
1
53
0
3
Order By: Relevance
“…High protein intake has also been reported to have other positive health outcomes including effects on total cholesterol and triacylglycerol and better lipid results which encourages the recommendation of high protein intake to patients with type 2 diabetes [34]. The finding that a higher intake of carbohydrate is associated with higher BMI and that lower intake is associated with lower BMI has been documented in majority of prospective experimental studies [13,14,35]; which reported weight loss effects of low carbohydrate diets. However, a study in Korea [10] did not find any association between carbohydrate intake and obesity.…”
Section: Discussionmentioning
confidence: 87%
“…High protein intake has also been reported to have other positive health outcomes including effects on total cholesterol and triacylglycerol and better lipid results which encourages the recommendation of high protein intake to patients with type 2 diabetes [34]. The finding that a higher intake of carbohydrate is associated with higher BMI and that lower intake is associated with lower BMI has been documented in majority of prospective experimental studies [13,14,35]; which reported weight loss effects of low carbohydrate diets. However, a study in Korea [10] did not find any association between carbohydrate intake and obesity.…”
Section: Discussionmentioning
confidence: 87%
“…Eighteen studies were randomized controlled trials, 17,21-37 three were non-randomized controlled clinical trials, 15,38,39 16 were single-arm intervention studies, 16,[18][19][20][40][41][42][43][44][45][46][47][48][49][50][51] two were retrospective case series analyses, 14,52 and two were case reports. 53,54 Thirty-four studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][32][33][34][36][37][38][43][44][45][46]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In 2012, he began to offer dietary advice11 recommending that newly diagnosed patients cut down or avoid not just sugars but also starchy carbohydrates like bread, pasta, rice, and potatoes. Instead, he encouraged them to eat green vegetables, meat, fish, eggs, and nuts as well as whole fat dairy products and olive oil.…”
Section: Evidence Lackingmentioning
confidence: 99%
“…He now monitors more than 100 patients who have been on a low carb diet for over two years and has published some results 11. He recently launched a free video course for doctors (www.dietdoctor.com/low-carb/for-doctors).…”
Section: Evidence Lackingmentioning
confidence: 99%